Transnational migration and the new subjects of work : transmigrants, hybrids and cosmopolitans - Ozkazanc-Pan, Banu, 1975- (Bristol : Bristol University Press, 2019)
In an increasingly globalized world, mobility is a new defining feature of our lives, livelihoods and work experiences. This book is a first in utilising transnational migration studies as a new theoretical framework in management and organization studies. Ozkazanc-Pan presents a much-needed new concept for understanding people, work and organizations in a world on the move while attending to growing inequality associated with work in changing societies.
Title from publisher's bibliographic system (viewed on 19 Mar 2021).
Keywords: Emigration and immigration; Transnationalism